I'm free but I'll comply with your request: generalization and multidimensional effects of the "evoking freedom" technique. Issue 1 (22nd January 2013) - Guéguen, Nicolas; Joule, Robert‐Vincent; Halimi‐Falkowicz, Séverine; Pascual, Alexandre; Fischer‐Lokou, Jacques; Dufourcq‐Brana, Maya
Abstract The "evoking freedom" technique is a verbal compliance procedure that solicits someone to comply with a request by simply telling them they are free to accept or to refuse the request. The measure of the efficiency of this technique on compliance with large samples and the evaluation of its influence on various requests was tested in the first set of experiments. This technique was found to be efficient in increasing the number of people who agreed to give money to a requester, the number of smokers who agreed to give a cigarette, passersby who agreed to respond to a survey, and homeowners who agreed to buy pancakes. In the second set of experiments in which the mode of interaction between the requester and the person solicited was tested, the "evoking freedom" technique was found to be associated with greater compliance with a request addressed by mail and through face‐to‐face, phone‐to‐phone, or computer‐mediated interaction. The third set of experiments tested the effect of semantic variations of the "evoking freedom" technique and the weight of the repetition of the semantic evocation of freedom. These later experiments that used various phrases evoking the freedom to comply were found to be associated with greater compliance. Moreover, a double evocation of freedom was associated with even greater compliance than a single evocation. The importance of this technique for commitment communication is discussed.